The Impact of Kyoto Protocol on Environment Quality in the Free Trade Era: The Case of G20 Countries - Buanawaty, Puspaning; Hastiadi, Fithra Faisal (International Journal of Economics and Financial Issues, 2017)
The impact of trade openness on environment is not easy to be figured out. The scale and technique effects of trade tend to have opposite direction, while the composition effect depends on the “comparative advantage” of a country. One way to avoid the world’s emission level is the ratification of Kyoto Protocol in 1997. This study aims to analyze the impact of trade openness and Kyoto Protocol on CO2 emission level. This research employs macroeconomics data in G20 countries from 1996 to 2008 by using OLS with gravity instrument variable model from G20 countries trade flows. The estimation results indicate that trade openness has positive and significant effect on CO2 emissions level. Meanwhile, Kyoto Protocol has insignificant effect on CO2 emissions level, thereby signifying the ineffectiveness of the Protocol’s implementation. Keywords: trade openness; Kyoto Protocol; CO2 emissions. JEL Classifications: F18, F53, Q54